(untitled) (Journal of the College of Basic Education, 2022)
The current research aims at evaluating the counseling records from the educational counselors’ point of view in secondary schools, through: constructinga research tool, evaluating the counseling records from the counselors’ point of view, and identifying the difference in evaluating the counseling records for educational counselors according to the gender variable (males, females). The difference in evaluating the guidance records of educational counselors is known according to the variable years of service (less than 15 years, more than 15 years. The researcher has relied on the analytical descriptive approach, and a list of criteria was prepared, which the researcher has relied on evaluating the extension records and presenting them to educational specialists. and calendar). It includes (40) items, and for each field (10) items. After the researcher confirmed the validity and reliability of the questionnaire, the researcher applied it to the research sample, who are the educational counselors in secondary schools in the city of Baqubah, the center. The research sample reached (220) mentors and counselors. After collecting and unpacking the questionnaires and obtaining the required data, and using the statistical bag to process the data, the results of the research were reached, including: - The first objective was achieved by constructing a research tool. The sample of this research confirms that the guidance records are clear and of great importance to the educational advisor. The existence of a statistically significant difference in favor of the educational counselors. There is no statistically significant difference for the variable years of service.In light of the results, the research came out with a set of recommendations and suggestions. Recommendations: Enriching the special information about the student to know the aspects that the educational counselor needs Opening courses for educational counselors on how to fill in the indicative records. Suggestions: Conducting a study to evaluate the educational counselor’s guide. Conducting a study to evaluate the work of the educational counselor